Analisis Strategi Integrated Marketing Communication dalam Penerimaan Peserta Didik Baru di Lembaga Pendidikan - Kuswantoro, Kuswantoro (Jurnal Kependidikan, 2016)
Abstract Educational institutions in general public schools rarely use marketing strategies in getting new students. This is due to one of them because the public school when the acceptance of new learners have been flooded with new prospective students, but different things happen in the average of private schools. The purpose of this paper is to examine how Integrated Marketing Communication (IMC) which consists of advertising, sales promotion, public relations & publicity and direct marketing, of New Student Admissions (PPDB) in private schools, especially the newly established private schools. Due to the reality in society many public perceptions that private schools are less interested in society because they think that private schools do not have good quality compared to state schools. For that it needs new breakthroughs to increase the number of new learners in accordance with the target expected by the educational institution is through Integrated Marketing Communication (IMC). Abstrak Lembaga pendidikan secara umum terutama di sekolah-sekolah negeri jarang sekali menggunakan strategi marketing dalam mendapatkan siswa-siswi baru.Ini disebabkan salah satunya karena sekolah negeri ketika penerimaan peserta didik baru sudah kebanjiran calon siswa baru, tetapi hal berbeda terjadi di rata-rata sekolah swasta.Tujuan penulisan ini adalah mengkaji bagaimana Integrated Marketing Communication (IMC) yang terdiri dari advertising, sales promotion, public relation & publicity serta direct marketing, terhadap Penerimaan Peserta Didik Baru (PPDB) di sekolahsekolah swasta terutama sekolah swasta yang baru berdiri.Karena realita yang terjadi di masyarakat banyak persepsi-persepsi masyarakat bahwa sekolahsekolah swasta kurang di minati oleh masyarakat karena menganggap bahwa sekolah-sekolah swasta tidak memiliki kualitas yang bagus di bandingkan sekolah-sekolah negeri.Untuk itu perlu adanya terobosan-terobosan baru guna meningkatkan jumlah peserta didik baru sesuai dengan target yang diharapkan oleh lembaga pendidikan tersebut yaitu melalui Integrated Marketing Communication (IMC).